THE IMPACT OF NON-TRADITIONAL TYPES OF FLOUR ON THE FORMATION OF CONSUMER PROPERTIES OF WAFERS - L. Z. Gabdukaeva; O. A. Reshetnik (Современная наука и инновации)
Flour confectionery products are high-calorie products with a pleasant taste and attractive appearance. The high nutritional value of flour products containing a significant amount of carbohydrates, fats, and proteins, is primarily due to the nutritional and biological value of the raw materials used. A promising direction to improve the nutritional value of flour confectionery products is the development of recipes from non-traditional types of flour, characterized by a high content of proteins, vitamins, mineral compounds, dietary fiber.